MANAJEMEN ORGANISASI SANTRI DALAM MEWUJUDKAN PONDOK PESANTREN JAGAD ‘ALIMUSSIRRY YANG LEBIH BERSIH, SEHAT, DAN AMAN) - Riyan Sisiawan Putra; Oki Safitri (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2023)
This study aims to determine the process of the Executive Board of Santri Pondok Pesantren Jagad 'Alimussiry (BES PPJA) in realizing cleaner, healthier Islamic boarding schools and safe. The type of research used in this research is descriptive method by explaining and describing the series of organizational management carried out by BES PPJA. Data collection was carried out through observation, interviews, and studies documentation, which among other things refers to data sources from BES PPJA management. Results this study explains that the ministry of K2S and the ministry of security and order able to boost students to maintain cleanliness and safety. It shows that organizational management provides an important role in realizing the cottagea cleaner, healthier, and safer pesantren. Keywords: Management Organization, Clean, Healty, and Safety